A round-robin gamma stereotactic radiosurgery dosimetry interinstitution comparison of calibration protocols - Drzymala, R E; Alvarez, P E; Bednarz, G; Bourland, J D; DeWerd, L A; Ma, L; Meltsner, S G; Neyman, G; Novotny, J; Petti, P L; Rivard, M J; Shiu, A S; et al. (Medical physics, 2015)
PURPOSE: Absorbed dose calibration for gamma stereotactic radiosurgery is challenging due to the unique geometric conditions, dosimetry characteristics, and nonstandard field size of these devices. Members of the American Association of Physicists in Medicine (AAPM) Task Group 178 on Gamma Stereotactic Radiosurgery Dosimetry and Quality Assurance have participated in a round-robin exchange of calibrated measurement instrumentation and phantoms exploring two approved and two proposed calibration protocols or formalisms on ten gamma radiosurgery units. The objectives of this study were to benchmark and compare new formalisms to existing calibration methods, while maintaining traceability to U.S. primary dosimetry calibration laboratory standards. METHODS: Nine institutions made measurements using ten gamma stereotactic radiosurgery units in three different 160 mm diameter spherical phantoms [acrylonitrile butadiene styrene (ABS) plastic, Solid Water, and liquid water] and in air using a positioning jig. Two calibrated miniature ionization chambers and one calibrated electrometer were circulated for all measurements. Reference dose-rates at the phantom center were determined using the well-established AAPM TG-21 or TG-51 dose calibration protocols and using two proposed dose calibration protocols/formalisms: an in-air protocol and a formalism proposed by the International Atomic Energy Agency (IAEA) working group for small and nonstandard radiation fields. Each institution's results were normalized to the dose-rate determined at that institution using the TG-21 protocol in the ABS phantom. RESULTS: Percentages of dose-rates within 1.5% of the reference dose-rate (TG-21+ABS phantom) for the eight chamber-protocol-phantom combinations were the following: 88% for TG-21, 70% for TG-51, 93% for the new IAEA nonstandard-field formalism, and 65% for the new in-air protocol. Averages and standard deviations for dose-rates over all measurements relative to the TG-21+ABS dose-rate were 0.999±0.009 (TG-21), 0.991±0.013 (TG-51), 1.000±0.009 (IAEA), and 1.009±0.012 (in-air). There were no statistically significant differences (i.e., p>0.05) between the two ionization chambers for the TG-21 protocol applied to all dosimetry phantoms. The mean results using the TG-51 protocol were notably lower than those for the other dosimetry protocols, with a standard deviation 2-3 times larger. The in-air protocol was not statistically different from TG-21 for the A16 chamber in the liquid water or ABS phantoms (p=0.300 and p=0.135) but was statistically different from TG-21 for the PTW chamber in all phantoms (p=0.006 for Solid Water, 0.014 for liquid water, and 0.020 for ABS). Results of IAEA formalism were statistically different from TG-21 results only for the combination of the A16 chamber with the liquid water phantom (p=0.017). In the latter case, dose-rates measured with the two protocols differed by only 0.4%. For other phantom-ionization-chamber combinations, the new IAEA formalism was not statistically different from TG-21. CONCLUSIONS: Although further investigation is needed to validate the new protocols for other ionization chambers, these results can serve as a reference to quantitatively compare different calibration protocols and ionization chambers if a particular method is chosen by a professional society to serve as a standardized calibration protocol.
Keywords: Spojené státy americké; Gamma Rays; Phantoms, Imaging; Radiotherapy Dosage; celková dávka radioterapie; Radiometry; záření gama; vzduch; radiometrie; United States; Air; radiochirurgie; klinické protokoly; Radiosurgery; voda; Water; Clinical Protocols; fantomy radiodiagnostické; kalibrace; Calibration